Acceptance and Commitment Therapy for the Treatment of Music Performance Anxiety: A Pilot Study with Student Vocalists - Juncos, David G.; Heinrichs, Glenn A.; Towle, Philip; Duffy, Kiera; Grand, Sebastian M.; Morgan, Matthew C.; Smith, Jonathan D.; Kalkus, Evan (Frontiers in Psychology, 2017)
This study investigated the use of Acceptance and Commitment Therapy (ACT) as a treatment for music performance anxiety (MPA) in an uncontrolled pilot study. ACT is a newer, “third-wave” therapy that differs from previous MPA treatments, because its goal is not to reduce symptoms of MPA. Rather, ACT aims to enhance psychological flexibility in the presence of unwanted symptoms through the promotion of six core processes collectively known as the ACT “Hexaflex.” A small group of student vocalists (N=7) from an elite choral college were recruited using objective criteria for evaluating MPA. Participants received 12 ACT sessions, and their baseline functioning served as a pre-treatment control. Treatment consisted of an orientation to ACT, identifying experientially avoidant behaviors, facilitation of Hexaflex processes, group performances in which valued behaviors were practiced in front of one another, meditations, homework, and completion of self-report measures before, during, and after treatment (at a one-month and three-month follow-up). Improvements were observed in participants’ cognitive defusion, acceptance of MPA symptoms, and psychological flexibility at post-treatment and follow-ups. Students also appeared to improve their performance quality and reduce their shame over having MPA. These results add to existing research suggesting ACT is a promising intervention for MPA, while also highlighting how vocal students may be less impaired by physical MPA symptoms.